1992
DOI: 10.1111/j.1432-1033.1992.tb17239.x
|View full text |Cite
|
Sign up to set email alerts
|

A high‐resolution solid‐state 13C‐NMR study on crystalline bovine heart cytochrome‐c oxidase and lysozyme

Abstract: We have recorded 100.6-MHz high-resolution solid-state ' 3C-NMR spectra of crystalline cytochrome-c oxidase from bovine heart muscle and hen egg-white lysozyme, to compare conformation and dynamics of a typical membrane-protein complex with those of lysozyme. The absence of severe interference with the solid-state 13C-NMR spectra, from both the line broadenings from paramagnetic centers and overlapping of intense detergent signals, provided spectral resolution of 3C-NMR feature of cytochrome-c oxidase crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The weak amide III intensity in the frequency region between 1235and 1240 cm™1 and the stronger intensity around 1300 cm™1 suggest a small population of the /3-sheet and a larger population of -helix, respectively (Lippert et al, 1976). The large content of -helix is consistent with the results from circular dichroism (Urry et al, 1967), solidstate NMR (Tuzi et al, 1992), and the primary structure (Frey et al, 1985) as well as the amide I Raman band described above. Lippert et al (1976) proposed a method for estimating the secondary structure distribution of proteins from Raman spectra.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The weak amide III intensity in the frequency region between 1235and 1240 cm™1 and the stronger intensity around 1300 cm™1 suggest a small population of the /3-sheet and a larger population of -helix, respectively (Lippert et al, 1976). The large content of -helix is consistent with the results from circular dichroism (Urry et al, 1967), solidstate NMR (Tuzi et al, 1992), and the primary structure (Frey et al, 1985) as well as the amide I Raman band described above. Lippert et al (1976) proposed a method for estimating the secondary structure distribution of proteins from Raman spectra.…”
Section: Discussionsupporting
confidence: 80%
“…(1) All the observed protein modes exhibited neither frequency shifts nor intensity changes upon the redox changes of the metal centers. This is in consequence with the results from solid-state NMR studies which detected no difference in protein signals between the resting and fully reduced states (Tuzi et al, 1992). Presumably, the redox-dependent conformational change of the protein is localized, and its range is considerably small compared with a large molecular size of this enzyme.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The resemblance between the selective narrowing of the lysyl 13 C ⑀ and 13 C ␦ resonances in the solid-state 13 C-NMR spectra of parvalbumin and the narrowing of the same carbon resonances in poly(Llysine), at increasing hydration, suggests that in both cases these specific effects involve an increase in the mobility of the lysyl side chain as a whole. A solid-state 13 C-NMR study of crystalline (fully hydrated) lysozyme showed that the lysyl 13 C ⑀ resonances in the 41 ppm region of the spectrum display a relatively short longitudinal relaxation time of 0.4 s (mean value), indicating rapid tumbling in the 10 ns time range (Tuzi et al, 1992). Similarly, the T 1 values of the 13 C ⑀ resonances of hydrated poly(L-lysine) powders (h up to 0.5) are in the 0.2-0.4 s range (at h ϭ 0.5, T 1 ϭ 0.36 s), indicating motions of the lysyl polar heads in the 10 ns.…”
Section: Sharpening the 13 C Resonances Upon Hydrationmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] Solidstate NMR methods can probe internal dynamics in the absence of the overall molecular tumbling, using anisotropic line shape analysis and relaxation measurements. [28][29][30][31] In solid-state NMR, the anisotropic resonance frequency depends on the orientation of the molecular frame with respect to the static magnetic field.…”
Section: Introductionmentioning
confidence: 99%